Sensing Salvation in the Gospel of John : The Embodied, Sensory Qualities of Participation in the I Am Sayings - Hanger, Jeannine Marie, (Biblical Interpretation Series ;, 2023)
Recent scholarship focused on the role of embodiment within cognition and communication reminds us that part of how we "know" is through our physical senses. We only know the softness of a kitten by touching its fur, or the tastiness of bread by eating. How might this influence our understanding of biblical texts, such as Jesus's claim, "I am the bread of life," and the invitation to eat? This study explores the I am sayings of John's Gospel, their sensory elements providing an imaginative entry into the narrative and contributing tangible value to the participatory theology of the Fourth Gospel.